2015
DOI: 10.1177/0044118x15604341
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Participation in Youth Organizations: Relationships With Identity and Sense of Sociopolitical Control

Abstract: Through a cross-sectional design, this study examines whether practices of active participation (AP; that is, opportunities for decision making and leadership) and quality of relationships (QR) established between members of youth organizations (i.e., affective and instrumental support) relate to dimensions of youth`s identity (i.e., personal purpose, personal meaning) and sense of sociopolitical control (i.e., leadership, political efficacy). Participants (n = 347; 17-26 years) were drawn from 38 youth organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 51 publications
(152 reference statements)
1
8
0
Order By: Relevance
“…They state that anti-Blackness and anti-immigrant sentiments are connected. What we found in our study is aligned with other literature on YO that demonstrated how youth activism heightened awareness about society, increased relationships with adults and each other, and was beneficial in improving mental health and academic success (Christens & Dolan, 2011; Martínez et al, 2017; Ortega-Williams et al, 2020). What is significant about Neon’s quote is that we found that youth not only demonstrated an acute awareness of an oppressive white power structure, but also how one navigated their own positionality and privilege.…”
Section: Discussionsupporting
confidence: 90%
“…They state that anti-Blackness and anti-immigrant sentiments are connected. What we found in our study is aligned with other literature on YO that demonstrated how youth activism heightened awareness about society, increased relationships with adults and each other, and was beneficial in improving mental health and academic success (Christens & Dolan, 2011; Martínez et al, 2017; Ortega-Williams et al, 2020). What is significant about Neon’s quote is that we found that youth not only demonstrated an acute awareness of an oppressive white power structure, but also how one navigated their own positionality and privilege.…”
Section: Discussionsupporting
confidence: 90%
“…It is these positive interactions between the dominant and migrant cultures that can help people reach across diversity and commit to each other. A second, more general policy implication is to recognise that identity is central to understanding behaviour (Hatch, Schultz, and Skov 2015;Martinez, Loyola, and Cumsille 2017). The evidence from this study is that youth attitudes can be influenced by enacted behaviour, even if initial engagement by some participants is somewhat reluctant.…”
Section: A Youth and Community Development Frameworkmentioning
confidence: 81%
“…The development of human resources in non-profits encompasses training and development, organizational development, career development, and community development. With the aim of ensure youth organizational sustainability, the quality of participation in youth organization leads powerful effects of the quality of the relational context of youth programs and organization (Martinez et al, 2017) Despite the existing literature on human resource development in profit and non-profit organizations, there is a gap in understanding the specific differences and challenges in human resource development within youth organizations. While studies have examined the importance of human resource development in driving organizational strategies and administrative management (Mondy & Noe, 1999), there is limited research on the unique needs and approaches to human resource development in youth organizations.…”
Section: Discussionmentioning
confidence: 99%